Scientific foundations and practical applications of periodization - Haff, G. G. (Human Kinetics, 2025)
The concept of periodization is not new, with the precursors of periodized training dating back more than 2,000 years ago. But it is now obvious that the holistic development of an athlete encompasses more than their physical and tactical training. Scientific Foundations and Practical Applications of Periodization is the first book of its kind designed to optimize sport performance by integrating both classic and modern periodization theories with recovery methodologies, nutritional interventions, and athlete monitoring guidelines.